Efikasi Diri Mahasiswa Pada Perkuliahan Matematika Diskrit - Farida, Anisatul; Indah, Ratna Puspita (Pendidikan Matematika Universitas PGRI Yogyakarta, 2023)
The purpose of this qualitative research is to describe in detail the profile of students' self-efficacy in dealing with discrete mathematics courses. The subjects of this study were 21 students of class TI21A4 Informatics Engineering Study Program, Duta Bangsa University, Surakarta, who were taking a Discrete Mathematics course. The information gathering tool consisted of a self-efficacy questionnaire and a guide for interview sessions. Participants filled out a questionnaire related to self-efficacy. The output of the self-efficacy questionnaire showed that 5% of students showed a very high level of self-efficacy, 39% had a high level of self-efficacy, 33% had a moderate level of self-efficacy, and 23% experienced a low level of self-efficacy. After that, 6 students were selected to be research subjects, consisting of 2 students each with high, medium, and low self-efficacy levels. Students with high and medium self-efficacy in solving Discrete Mathematics questions do not give up easily, while students with low self-efficacy give up easily when solving these problems. Students with high and moderate self-efficacy have been able to learn independently, while students with low self-efficacy have not been able to learn difficult Discrete Mathematics material independently and need guidance from the lecturer. Even so, students with high, medium, and low self-efficacy were able to complete assignments and submit assignments on time. Students with low self-efficacy, their learning efforts are less than optimal for various reasons so that they have not been able to achieve the targeted learning achievements. While students with high and moderate self-efficacy are already optimal with regard to their learning efforts Keywords: self-efficacy; student; discrete mathematics